The impact of FinTech adoption, digital payments, and transparency on zakat towards income contributions - Safiyuddin, Fatin Syazwani; Razali, Nur Danira Fakhira; Musaddad, Hafirda Akma; Mahmad Nasir, Nadiah (Journal of Islamic, Social, Economics and Development, 2026)
Zakat on income is a fundamental Islamic financial obligation that promotes social justice and assists marginalised communities. Despite well-organised zakat institutions in Malaysia, challenges persist regarding compliance, accessibility, and public trust. Financial technology (FinTech) has emerged as a potential mechanism to enhance zakat collection by improving convenience, efficiency, and transparency. This study examines the influence of FinTech adoption, digital payment systems, and transparency on zakat on income contributions among Muslim income earners in Penang. A quantitative design was used, involving 384 respondents selected through non-probability sampling. Data were analysed using descriptive and inferential statistics. Results indicate that FinTech adoption significantly enhances zakat contribution behaviour by improving ease of use and accessibility. Digital payment systems further increase the efficiency and frequency of payments, while transparency mechanisms such as real-time tracking and automated receipts) strengthen donor trust and compliance. The study highlights the critical role of digital innovation in modernising Islamic social finance and offers policy recommendations for enhancing zakat governance through Shariah-compliant FinTech solutions.